Relationship Between Communication And Outpatient Satisfaction At The Megang Sakti Health Center Musi Rawas District - Indanitry, Destya; Pebriani, Emi; Sulastri, Sulastri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Quality service is needed because it concerns the rights of every customer and health. Service quality and value have a direct impact on customers. Customer satisfaction is influenced by the quality of service experienced by customers (Nurul 2017). Patient satisfaction is created by the quality of health services so that good and quality health services will have a positive impact on health services, namely the creation of a well-established loyalty that forms word of mouth that benefits service providers (Gurning, 2018). This study aims to determine the relationship between communication and outpatient satisfaction at the Megang Sakti Health Center, Musi Rawas Regency. The method used is correlative analytic research with a cross-sectional approach, correlative analytic research design is research that connects one variable with another. The sample in this study amounted to 45 people. The results of the univariate test analysis that most of the respondents (46.7%) had poor communication, most of the respondents (42.2%) had low satisfaction, there was a relationship between communication and outpatient patient satisfaction at the Megang Sakti Health Center, Musi Rawas Regency. Researchers suggest to the Megang Sakti Health Center to provide knowledge about the importance of communication to patients so that it can increase Outpatient Patient Satisfaction at the Megang Sakti Health Center, Musi Rawas Regency.